Indonesia’s Place in the Research Landscape of Southeast Asia - Fiala, Dalibor (Unisia, 2022)
This article presents a scientometric analysis of 330,729 journal articles indexed in the prestigious Science Citation Index Expanded of the Web of Science database authored by researchers affiliated with institutions from five Southeast Asian countries (Indonesia, Malaysia, Philippines, Thailand, and Vietnam) and published in the first two decades of the 21st century (2001-2020). With a focus on Indonesia, we examined the scientific production of those five nations as well as the citedness of their research publications from both the static and dynamic perspectives and compared various indicators of countries in absolute and relative terms, including the socio-economic aspects of population size, gross domestic product, and research and development expenditures. The key findings are: a) the overall research production of all five countries has been growing, b) Indonesia is the weakest nation in all relative scientometric indicators except the average number of citations per paper, where it is ranked second, c) Malaysia is generally the leading nation, but Vietnam has the most remarkably positive development in both production and citedness, and d) the Philippines is extremely efficient in the mean number of citations per paper as well as per expenditure on research and development.